Analisis Distorsi Biaya dan Hidden Costs pada Produk Kompleks dan Standar UMKM Berbasis Activity-Based Management - Ikha Andriani; Ismayanti; Widia Wahyuni; Novitasari; Asriani Hasan (Jurnal Riset Akuntansi Politala, 2026)
Increased cost utilization in MSMEs is one of the factors that determine the development of a business, including the challenge of cost distortion due to the use of a traditional Cost of Goods Sold (COGS) system that is subjective and ignores the hidden costs of non-value-added activities. This study aims to analyze cost distortions and identify hidden costs in Cahaya Aluminium MSMEs using the Activity-Based Management (ABM) approach. The research method used is qualitative-descriptive with a single case study design and a descriptive-comparative approach. Primary data was obtained through in-depth interviews validated through triangulation of informal cost data. Data analysis techniques used thematic analysis, starting from data collection, data reduction through Activity-Based Management (ABM) activity coding, and using Activity-Based Cost (ABC) simulations presented in a comparison matrix. The results of the Activity-Based Costing (ABC) simulation showed significant cost distortions in the Kitchen Set (Complex Product) aspect, which experienced undercosting, and the Dish Cabinet (Standard Product), which experienced overcosting. These distortions were triggered by non-value-added activities such as rework and material return waiting time. Based on these results, it can be seen that Activity-Based Management (ABM) through material synchronization and supplier evaluation can improve the accuracy of HPP and operational efficiency for Cahaya Aluminium MSMEs